Modeling of C-SNARF-1 ph fluorescence properties: Towards calibration free optical fiber pH sensing for in vivo applications - Rutjaphan Kateklum (2018)
Copyright © 2018 by SCITEPRESS – Science and Technology Publications, Lda. All rights reserved Organic functions of the human body are related to biological constants. Variations of these constants, among them pH, induce pathological troubles. The general goal of our work is to fabricate a fluorescent pH sensor at the end of an optical fiber for in vivo pH measurements. One difficulty using fluorescence indicators is the need to perform an accurate calibration. In this communication, we present methods used to simplify and potentially avoid calibration procedures of fluorescence indicators. The first method concerns the simplification of calibration procedures making them independent of the indicator’s concentration, path length and equipment used. The second method concerns modelling the fluorescence emission of the molecules as a function of pH only. This model is used to fit the exact shape of C-SNARF-1 fluorescence spectra obtained at any pH. Subsequently, the pH of a solution can be computed with an accuracy of 0.1 pH unit without the calibration procedure employed up to now. These methods constitute the first steps toward calibration free pH measurements. They can be applied to any fluorescent indicator exhibiting a dual emission peak. As a conclusion, this is the first time that fluorescence properties of C-SNARF-1 are fully mathematically described.